Identifying Factors Associated with Changes in CD4+ Count in HIV-Infected Adults in Saskatoon, Saskatchewan - Kelsey Hunt; Prosanta Mondal; Stephanie Konrad; Stuart Skinner; Kali Gartner; Hyun J Lim (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: To assess the impact of clinical and social factors unique to HIV-infected adults in Saskatoon, Saskatchewan, regarding the rate of CD4+ count change, and to identify factors associated with a risk of CD4+ count decline.